Errors Analysis in Understanding Transformation Geometry Through Concept Mapping - Siti Napfiah; Yunis Sulistyorini (International Journal of Research in Education, 2020)
The concept map is a chart that illustrates an understanding of a particular series. In the concept map, there is a relationship between concepts in a certain material according to the conceptual that is in the mind of the person who made it. This research emphasizes the analysis of errors, namely conceptual errors, by involving the construction of concept maps.The purpose of this research is to identify the conceptual errors of students in understanding the Transformation Geometry material through concept mapping. The subjects were IKIP Budi Utomo Malang students who were taking the Transformation Geometry course. This research was descriptive qualitative research. The instrument used was the concept map of geometry transformation made by students. Based on the concept map made by students, there are some errors, which are as follows.The error of low ability students in constructing concept maps is that they cannot give proper connections between materials and include examples of questions that should not need to be included in the concept map. The error of medium ability students is that they do not provide a clear description of each material. High ability students do not have any errors but they are less similar in giving explanations to each material.